MANAGEMENT OF ORAL AND DENTAL DISEASES IN MEDICALLY COMPROMISED PATIENTS (Patient with Diseases of Cardiovascular System) - Afi Savitri Sarsito (Faculty of Dentistry, Universitas Indonesia, 2015)
The treatment of oral and dental diseases in healthy patients can be performed with general standard and usually do not cause problems. On the other hand treatment of oral and dental diseases in medically compromised patients, especially one with disease of cardiovascular system must be performed with specific standard or otherwis emay evoke serious problems. Therefore the treatment needs to be compromised with the condition of the patients as well as the medication they are taking. This paper explains the management of oral and dental diseases in patients with disease of cardiovascular system usually found such as hypertension, infective endocarditis, rheumatic fever and rheumatic heart diseases where the cooperation between dentist and internist is extremely recommended.